Reduction of selective polyaromatic nitrotriptycene via an azoxytriptycene intermediate under ambient conditions using a cobalt/cobalt oxide nanocomposite (CoNC). Issue 65 (24th June 2016) - Mohammad, Akbar; Mishra, Veenu; Chandra, Prakash; Mobin, Shaikh M.
Abstract : Selectively targeted polyaromatic 2-nitrotriptycene (M1 ) and 2, 6, 14-trinitrotriptycene (M2 ) were chosen as model substrates for demonstrating catalytic hydrogenation, under ambient conditions, using a cobalt/cobalt oxide based nanocomposite (CoNC ) as the catalytic material. Abstract : A cobalt-based nanocomposite (CoNC ) has been prepared from a recently reported single source molecular precursor (SSMP) [Co II (hep-H)(H2 O)4 ]SO4 (A ) (hep-H = 2-(2-hydroxylethyl)pyridine). The resulting nanocomposite material was characterized by using various physicochemical techniques such as XRD, SEM, EDAX, TEM and XPS spectroscopy. X-ray diffraction patterns show the weakly crystalline nature of the catalyst. This was also confirmed by the SAED pattern obtained from HR-TEM. XPS analysis reveals the formation of metallic cobalt and the cobalt oxide (CoO) nanocomposite.CoNC was employed for the facile catalytic hydrogenation of 2-nitrotriptycene (M1 ) and 2, 6, 14-trinitrotriptycene (M2 ) as model substrates under atmospheric reaction conditions, which otherwise takes place either with RANEY® Nickel, Pd/C or SnCl2 /HCl catalysts under harsh conditions. The mechanistic pathway reveals that the reduction ofM1 proceeds via the intermediacy of azoxy triptycene (III ) and N -hydroxylamine triptycene (IV ).